Nano-hardness and microstructure of selective laser melted AlSi10Mg scan tracks - Aboulkhair, Nesma T.; Tuck, Christopher; Maskery, Ian; Ashcroft, Ian; Everitt, Nicola (2015)
Selective laser melting (SLM) of aluminium alloys faces more challenges than other ongoing alloys such as stainless steels and titanium alloys because of the material’s properties. It is important to study single scan tracks if high density large parts are to be made since they are the primary building blocks. In this study, the geometrical features of AlSi10Mg tracks indicated keyhole mode melting domination. Chemical composition mapping and nanoindentation showed enhanced nano-hardness in SLM material over conventional material with no spatial variation. This is due to a homogeneous elemental distribution and fine microstructure developed by fast solidification.